A new species of Acantholycosa Dahl, 1908 (Aranei: Lycosidae) from the highlands of Sikhote-Alin Mountains, Maritime Territory of Russia - Omelko, M. M. (Acta biologica sibirica)
A new species of wolf spider, Acantholycosa voronoii sp. nov., collected among isolated screes in the highlands of Sikhote-Alin Mountains, is diagnosed, illustrated and described based on both sexes. The new species is related to A. irinae Fomichev & Omelko, 2020, a species recently described from a neighboring mountain; the two species differ in the conformation of copulatory organs and number of ventral spines on tibia I. A distribution map of all known Acantholycosa species in south of Maritime Territory is provided.